Development of a Curriculum for Minimally Invasive Spine Surgery (MISS). Issue 2 (April 2020) - Schmidt, Franziska A.; Wong, Taylor; Kirnaz, Sertac; Taboada, Néstor; Assaker, Richard; Hofstetter, Christoph; Kim, Jin-Sung; Parajón, Avelino; Taylor, Paul; Assous, Muhammed; Härtl, Roger
The purpose of this review is to describe how a curriculum for minimally invasive spine surgery (MISS) was developed and implemented. The authors discuss the curriculum roadmap, its target audience, and the educational process for teaching general skills and specific procedures in MISS. Initiated by AOSpine, a panel of experts within spinal surgery from multiple centers formed the minimally invasive spine surgery task force. Together, task force members redefined the standards and milestones of the MISS education and training. Therefore, we conclude that the MISS task force created a structured curriculum which will have a positive influence on daily practice for surgeons and patients worldwide.